Swift's Alberti? The Geometrical Comedy of Gulliver's Travels - Selena Özbas (Ideas: Journal of English Literary Studies)
This article propounds that Jonathan Swift’s Gulliver’s Travels develops a geometrical comedy in the Albertinian fashion. Starting with a specific reference to Momus in Puppet-Show, it will be maintained that Swift refers to an earlier tradition of criticism and transfers it to his prose writing. To explore this point, the article will draw on the Italian Renaissance humanist, satirist, and architect Leon Battista Alberti’s Momus and De Pictura. It will be suggested that there is a corollary between the exilic vision of the picaresque anti-hero and the definitive quality of the centric ray which establishes the centre of meaning in painting in Alberti. In accordance, it will be maintained that Swift adapts Alberti’s critical rendition of the Momus story as a geometrical metaphor for linear perspective. Although Momus does not directly appear as part of the dramatis personae in Gulliver’s Travels, Lemuel Gulliver emerges as an eighteenth-century successor to Alberti’s geometrical designs since Swift adapts the Renaissance humanist’s method of geometrical optics which reveres ocularcentrism. By these standards, it will be propounded that this method informs the comedic programme of Gulliver’s Travels. In accordance, the conclusion draws on the point that Swiftian comedy owes a considerable debt to the mimetic concerns of Renaissance humanism which signals the birth of a posthumanist comedy through a re-mapping of Albertinian perspectivism.